Linguistic support as a key element in the development of distance multimedia educational systems: composition and structure - Fabian, M.; Herman, V.; Varekh, N. V.; Kumeda, O.; Hotsalyuk, A.; Варех, Н. В. (Centro Universitario Curitiba, 2025)
Objective: of the article is distance multimedia learning systems. Methods: To solve the tasks and test the working hypotheses, the study used a set of theoretical methods and techniques adequate to the nature of the object under study: methods of system analysis, which were used at the stage of identifying the problem area, determining its relevance, setting goals and developing solutions; methods of terminological analysis, which were used in a comprehensive study of various scientific works on the research problem; methods of algorithmization and programming used to develop a data description format; methods of empirical research to obtain data on the functioning of the pattern recognition system and the automated assessment system. Results: The concept of a distance multimedia learning system is defined and the application of distance multimedia learning systems in higher education in the field of design is considered; the structure and composition of distance multimedia learning systems are studied; specific features of learning using distance multimedia learning systems are studied and identified; the specifics of user personalization in the multimedia space are considered; a format for describing data in distance multimedia learning systems is developed; principles of using a didactic model of a multimedia component in the linguistic support of distance multimedia learning systems are introduced. Conclusion: The definition of the concept of distance multimedia learning systems is given, the relevance of distance multimedia learning systems in relation to the educational environment is analyzed, methods of organizing distance education are studied, the principles of working with the learning system are structured; distance multimedia learning systems, the influence of multimedia on the student are structurally studied, options for the development of e-learning by means of multimedia, virtual and augmented reality, artificial intelligence technologies and neural networks are shown; the importance of independent work both in the multimedia system and for learning in the field of creative areas of learning is determined; principles and stages of creating distance learning complexes are developed, a number of criteria for assessing the quality of learning systems are derived, the importance of developing usability, adaptability and interactivity of the system is analyzed, and the composition of the specialists necessary to improve the quality of developing distance multimedia learning systems in the field of creative areas of learning is determined; principles for creating distance multimedia learning systems have been formulated, a set of linguistic support tools has been proposed: an information model of an image recognition system, an automated assessment model, a data description format has been developed to enable automated monitoring of creative practical assignments of students.
Keywords: education; distance multimedia learning systems; terminological analysis; linguistic support